RETRACTED: Synthesis and characterization of new D-π-D type Schiff base ligands (Retracted Article) - Karaoglan, G. K.; Erden, I.; Avciata, U. (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2009)
Two Schiff bases of D-p-D type (L-1 and L-2) have been successfully synthesized by the reaction of 3,3'-dimethylnapthide and 3,3',5,5'-tetramethylbenzidine with 4-(dimethylamino)cinnamic aldehyde. The ligands L-1 and L-2 have been characterized by IR, UV-visible, H-1 NMR and fluorescence spectra, as well as, TGA-DSC-DTG, elemental analyses and mass spectra.
Keywords: COMPLEXES; NICKEL(II); DERIVATIVES; COBALT(II); EMITTERS; CRYSTAL; Chemistry